(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Flax is cultivated on small areas in Latvia. Flax gives dual-purpose production – fibre and seeds. Latvian flax has a high fibre and seed quality. The quantity of flax fibre and seed yield depends on many factors. Several qualitative and quantitative traits, such as technical stem length, resistance to lodging, vegetation period, yield of straw and seeds, fibre and oil content and quality were evaluated. For the further development of Latvian economy flax varieties and hybrids of Latvian origin are an important goal. Fibre flax varieties 'Blue di Riga', 'Priekuļu 665', 'Ošupes 30' and breeding lines 'S-64-17-93' and 'L11-11/11-94' are valuable material containing a qualitative and quantitative indicators of variety. 92 Latvian accessions of flax hybrids have been evaluated, and 12 accessions with the best seed and straw yield have been selected for further DNA analysis. This will simplify and accelerate the selection of new valuable hybrids that will provide particular advantages in agriculture. The genetic analysis of DNA determines the kinship and diversity of flax varieties and breeding lines which can be used further in flax breeding.